An N-ethylmaleimide-sensitive cytosolic factor necessary for nuclear protein import: requirement in signal-mediated binding to the nuclear pore (The Rockefeller University Press, 1990)
We described previously an assay for authentic nuclear protein import in vitro. In this assay, exogenous nuclei are placed in an extract of Xenopus eggs; a rhodamine-labeled protein possessing a nuclear localization signal is added, and fluorescence microscopy is used to measure nuclear uptake. The requirement in this system for a cytosolic extract suggests that nuclear import is dependent on at least one cytosolic factor. We now confirm this hypothesis. Treatment of the cytosol with N-ethylmaleimide (NEM) abolishes nuclear protein import; readdition of a cytosolic fraction to the NEM-inactivated extract rescues transport. Thus, at least one NEM-sensitive factor required for transport is supplied by the cytosol. This activity, called nuclear import factor-1, or NIF-1, is ammonium-sulfate-precipitable, protease- sensitive, and heat-labile; it is therefore at least partly proteinaceous. NIF-1 stimulates, in a concentration-dependent manner, the rate at which individual nuclei accumulate protein. The effect of NIF-1 is enhanced by a second cytosolic NEM-sensitive factor, NIF-2. Earlier we identified two steps in the nuclear import reaction: (a) ATP- independent binding of a signal-sequence-bearing protein to the nuclear pore; and (b) ATP-dependent translocation of that protein through the pore. We now show that NEM inhibits signal-mediated binding, and that readdition of NIF-1 restores binding. Thus, NIF-1 is required for at least the binding step and does not require ATP for its activity. NIF-1 may act as a cytoplasmic signal receptor that escorts signal-bearing proteins to the pore, or may instead promote signal-mediated binding to the pore in another manner, as discussed.